The “Evaluation of compliance to “Discharge Instruction” among Post Myocardial Infarction Patients at Teaching Hospital Hyderabad, Pakistan” - Luhana, Ranjeeta (Journal of University Medical & Dental College, 2024)
Background: A Discharge instruction is one of an important factor affecting on Post Myocardial Infarction (MI) patient. Objective: The study was evaluated the compliance to discharge instructions, and its impact upon life style changes among patients of post myocardial infarction. Methodology: A total 180 participants in this cross-sectional descriptive study and this study was conducted at Cardiology Outpatient Department (OPD) Liaquat University Hospital Hyderabad. The study time was 6 months from June 2021 to November 2021. Data was collected from OPD patients having had their first attack of myocardial infarction after being discharge from the hospital. Data was collected by self-structured questionnaire and analyzed by Statistical Package for Social sciences (SPSS) version 20.0 and results presented as frequency and percentage. Results: This study was found that majority of patients are primary or secondary level educated and they have knowledge about health status. In contrast, patients were not completely finished smoking and alcohol consumption. Patients have known smoking and alcohol both dangerous for health. In addition, majority of patients have not checked BMI and they have not gone for walk regularly. Exercise and Body Mass Index (BMI) both elements plays important role in Post MI patients because it can control and manage the development of atherosclerosis. Conclusion: We find that discharge education play very important role for cardiac patients. So, organized and structured discharge education can impact on cardiac patients as well as minimize recurrent attack, hospitalization, hospital readmission and revisits. Key words: Cardiovascular Diseases, Myocardial Infarction, Discharge Education